Assessment of the medical records management system of a level 3 hospital in Las Pinas City - Francia, Lariza S.
The medical records management system of a level 3 hospital in Las Pinas City was assessed in terms of physical structure, processes involved, completeness of records, and documentation in order to determine the strengths, weakness and readiness of the hospital for its next Philhealth audit. Data was gathered through interview, observation and use of a tool for medical records review. Prior to data collection, pre-test for the tool was done. Out of 370 medical records assessed, 15 (4.05%) are completely filled up. The past of the chart found to have the lowest percentage of items filled up is the clinical history form, having 63% of its items filled up. Major factors contributing to this are the current process or system in place for managing records, doctors and medical records personnel, clinical history forms and quality management in the hospital. Based on the results, the hospital needs to improve its current system for evaluating medical records and ensuring their completeness. In addition, the quality management system in the hospital should be revised and strengthened. The staff should be trained and regularly updated regarding good practices in medical record management. Finally, an ongoing medical records review should be put in place to ensure quality of medical records in the hospital.